A FALLACY IN ACCOUNTING FOR SPOILED GOODS. - Koch, Alfred P. (The Accounting Review, 1960)
The article discusses a fallacy in accounting for spoiled goods. Spoiled goods arise as a result of imperfections in manufacturing processes. The condition of the goods is such that it would not be economically feasible to correct the imperfections. As a consequence, the goods are sold as seconds at a loss. A loss due to spoilage may be charged to the job or production order on which the loss occurred or it may be absorbed indirectly by all jobs through charging such loss to manufacturing overhead control. If spoilage loss is not normal or a loss can be easily traced to a job which may be special in character, the loss should be charged to the job on which the loss occurred. If spoilage is normal because of the nature of the manufacturing process but irregular in amount from job to job, the loss arising from spoiled goods should be absorbed by all jobs by means of a predetermined manufacturing overhead rate. An exception may be taken to the treatment found in cost accounting publications whereby spoilage loss is absorbed indirectly by all jobs through charging such loss to manufacturing overhead.